Performance économique du Canada en 1985 : une bonne année - Landry, Jean-Luc (Assurances, 1986)
1985 was a good year for the Canadian economy, as economic activity increased by approximately 4% in real terms and inflation remained below 5%. This was achieved despite an almost complete lack of leadership in fiscal policy as an unusual number of Government budgets were not even voted during the year and as a banking system crisis absorbed most of the attention of the Bank of Canada. The author finds that the cyclical position of the Canadian economy is adequate and actually more favourable than that of the United States.